The Role of Islamic Work Ethics in Strengthening Halal Service Branding: A Study at Sharia Hotel X - Rachma Rizqina Mardhotillah; Mohamad Yusak Anshori; Denis Fidita Karya (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2025)
This study examines the determinants of behavioral intention toward halal tourism destinations by applying the Theory of Planned Behavior (TPB). Specifically, the research investigates the effects of attitude, subjective norm, and perceived behavioral control on tourists’ behavioral intention in the context of halal tourism destinations in Lombok, Indonesia. A quantitative research design was employed using a cross-sectional survey approach. Data were collected from Muslim and non-Muslim tourists who had visited or intended to visit halal tourism destinations and were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The measurement model assessment demonstrates satisfactory convergent and discriminant validity, as indicated by outer loading values exceeding the recommended threshold, Average Variance Extracted (AVE) values above 0.50, and strong internal consistency reflected by Cronbach’s alpha and composite reliability values. The structural model results reveal that attitude, subjective norm, and perceived behavioral control have positive and significant effects on behavioral intention. The R-square value indicates a substantial explanatory power of the model, while the f-square analysis confirms the varying effect sizes of each antecedent on behavioral intention. These findings highlight the importance of psychological and social factors in shaping tourists’ intentions toward halal tourism destinations. Practically, the results provide insights for destination managers and policymakers to design effective marketing strategies by strengthening positive attitudes, leveraging social influence, and enhancing tourists’ perceived control through accessible facilities and halal-friendly services. This study contributes to the growing body of halal tourism literature by empirically validating the TPB framework in a multi-group tourism context.